From Q/Non-Q Myocardial Infarction to STEMI/NSTEMI: Why It’s Time to Consider Another Simplified Dichotomy; a Narrative Literature Review - Avdikos, Grigorios; Michas, George; W. Smith, Stephen (Archives of Academic Emergency Medicine, 2022)
Acute coronary syndromes (ACSs) are classified as ST-segment elevation myocardial infarction (STEMI) and non-ST-segment elevation myocardial infarction (NSTEMI) based on the presence of guideline-recommended ST-segment elevation (STE) criteria on the electrocardiogram (ECG). STEMI is associated with acute total coronary occlusion (ATO) and transmural myocardial necrosis and is managed with emergent reperfusion therapy, and NSTEMI is supposedly synonymous with subendocardial myocardial infarction without ATO. However, coronary angiograms reveal that a significant proportion of patients with NSTEMI have ATO. Here, we review articles that studied the frequency and cardiovascular outcomes of ATO in NSTEMI patients compared with those without ATO. We discuss ECG patterns of patients with suspected acute myocardial infarction that do not fulfill STEMI criteria but are associated with ATO. Under-recognition of these atypical patterns results in delays to reperfusion therapy. We also advocate revision of the current STEMI/NSTEMI paradigm because consideration of STE, by itself, out of context of other clinical and ECG features, leads to the ECG diagnosis of STEMI when the ECG actually represents a mimic [“Pseudo-STEMI”], and suggest renaming the ACSs classification as the Occlusion Myocardial Infarction (OMI)/Non-Occlusion Myocardial Infarction (NOMI) paradigm.